COMMUNITY SATISFACTION INDEX ON HEALTH SERVICES AT PUSKESMAS KAMAL - DENI PURNOMO; SYAMSUL ARIFIN; NUR YADI (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
This study aims to determine the Community Satisfaction Index (IKM) for health services at the Kamal Health Center.The research method used is a quantitative approach with a descriptive approach. This study involved 98 samples and was taken by accidental sampling. The data collection technique uses a questionnaire, which is then carried out a simple linear regression test using 9 elements as listed in the Minister of Agriculture RB Number 14 of 2017 concerning Guidelines for the Preparation of Community Satisfaction Surveys. The results of the study concluded that the Community Satisfaction Index at the Kamal Health Center had run very well, with an IKM conversion value of 84.28. However, there are still shortcomings in indicators of resolution time, handling of complaints, suggestions and inputs. Meanwhile, based on the test results, the correlation coefficient between variable X and variable Y gets a value of 0.635, which means it has a positive influence. So it can be concluded that, the services provided by officers have a positive effect on the community satisfaction index at the Kamal Health Center.